Ameliorating effect of psychobiotics and para-psychobiotics on stress: A review on in vivo and clinical studies and mechanism of action - Mohammad Mahdi Gholian; Arash Babaei; Fatemeh Zendeboodi; Amir M. Mortazavian; Vahid Koushki (Heliyon)
Chronic stress can negatively affect cognitive ability, behavioral functions, and gut microbiota balance. The gut microbiota communicates with the brain through the gut-brain axis to influence brain responses and behavior. The positive effects of psychobiotics and para-psychobiotics (viable and non-viable probiotics, respectively) on decreasing stress and stress-related disorders have been approved, previously. It has been suggested that the benefits of such probiotics are provided through different probable routes including the hypothalamic-pituitary-adrenal (HPA) axis, the immune system modulation, and the production of neurotransmitters. The recent review aims to explore the different potentials of psychobiotics and para-psychobiotics based on recent literature. The recent literature revealed that psychobiotics and para-psychobiotics could be considered as an alternative to psychotropic drugs which present dependence and side effects compared to chemical drugs.